Granulocytic sarcoma of the breast without development of bone marrow involvement: a case report - Quintero-Cuadra L Yolanda; Arrecillas-Zamora Myrna D; Vela-Chávez Teresa A; Fend Falko (BMC, 2009)
Abstract A 29-year-old woman presented with a breast tumor with a primary diagnosis of MALT lymphoma. A repeat biopsy revealed a hematological neoplasm with diffuse, Indian file, and targetoid patterns. The cells were intermediate size with eosinophilic granules; the immunophenotyping showed monocytic differentiation, and no lymphoepithelial lesion was observed. The diagnosis was granulocytic sarcoma. Three different bone marrow biopsies were negative for neoplastic infiltration. After treatment, she developed secondary pancytopenia which contributed to her death 16 months after primary diagnosis. Granulocytic sarcoma of the breast is uncommon. A complete panel of immunohistochemistry is necessary to perform this diagnosis.